EKSPLORASI BUKTI DIGITAL PADA SMART ROUTER MENGGUNAKAN METODE LIVE FORENSICS - Abdul Rohman Supriyono; Bambang Sugiantoro; Yudi Prayudi (P3M Politeknik Negeri Cilacap, 2019)
Network devices as media file sharing and can be used as file servers have begun to appear, just as smart router devices can be used as file servers by adding USB Thumb drive as storage media. With the diversity of router devices, it becomes a challenge in digital forensic science when a case occurs by utilizing a smart router device related to file-sharing services. Then it is necessary to study the right method in investigating smart router devices. This paper discusses the use of the live forensics acquisition method in investigating smart router devices, against system log files related to file-sharing activities. In identifying the process of searching, recognizing, and documenting potential things as digital evidence of processing devices and digital media storage. The acquisition process uses two methods, namely the live acquisition method on the router device and physical acquisition on the device that is used as storage media on the smart router.